2005
DOI: 10.1086/431605
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Oral Typhoid Vaccine M01ZH09 Is Well Tolerated and Highly Immunogenic in 2 Vaccine Presentations

Abstract: The oral typhoid vaccine M01ZH09 is well tolerated and highly immunogenic in a single oral dose, with and without prevaccination with a bicarbonate buffer. Field studies to demonstrate protective efficacy are planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 21 publications
2
52
0
Order By: Relevance
“…We suspected that S. Typhi-specific antibodies (IgG, IgA, and IgM at early time points) were the immune opsonins primarily responsible for the observed increases in phagocytosis of S. Typhi. Previous studies showed that all subjects tested in the opsonophagocytosis assays produced IgG and IgA specific to S. Typhi lipopolysaccharide (LPS) following vaccination with ZH9 (21,22,31). All serum samples used in the opsonophagocytosis assays were heat treated (56°C; 30 min) to inactivate the complement system and remove its contribution to phagocytic uptake.…”
Section: Postvaccination Opsonins Increase Uptake Of Wild-type Smentioning
confidence: 99%
See 2 more Smart Citations
“…We suspected that S. Typhi-specific antibodies (IgG, IgA, and IgM at early time points) were the immune opsonins primarily responsible for the observed increases in phagocytosis of S. Typhi. Previous studies showed that all subjects tested in the opsonophagocytosis assays produced IgG and IgA specific to S. Typhi lipopolysaccharide (LPS) following vaccination with ZH9 (21,22,31). All serum samples used in the opsonophagocytosis assays were heat treated (56°C; 30 min) to inactivate the complement system and remove its contribution to phagocytic uptake.…”
Section: Postvaccination Opsonins Increase Uptake Of Wild-type Smentioning
confidence: 99%
“…However, both vaccines have drawbacks that necessitate the development of next-generation typhoid vaccines: Ty21a requires 3 or 4 oral doses, while Vi requires a needle injection, and refrigeration is necessary for both (13,14). Several next-generation vaccines, designed to optimize efficacy and simplify delivery, are currently in human trials, including a single-oral-dose typhoid vaccine, M01ZH09 (S. Typhi Ty2 ⌬aroC ⌬ssaV) (4,14,17,22,28,31,32,41).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This alternative technique has been used to preserve many biological products such as bovine pericardium (9,11) , human red blood cells (12) , epidermal keratinocytes (13) , amniotic membrane (14) , vaccines (15) and others.…”
Section: Dehydrationmentioning
confidence: 99%
“…Most vaccine researchers avoid the problem low gastric pH poses by coating their vaccine in a protective enteric capsule (e.g., Ty21a) or by coadministration of an antacid (usually sodium bicarbonate) at the time of immunization (17)(18)(19)(20)(21)(22). Preventing vaccine exposure to low pH increases the number of viable cells that reach the intestine and improves vaccine immunogenicity (22,23).…”
mentioning
confidence: 99%